A signature based on anoikis-related genes for the evaluation of prognosis, immunoinfiltration, mutation, and therapeutic response in ovarian cancer - Duan, Yiqi; Xu, Xiao (Frontiers in Endocrinology, 2023)
Background: Ovarian cancer (OC) is a highly lethal and aggressive gynecologic cancer, with an overall survival rate that has shown little improvement over the decades. Robust models are urgently needed to distinguish high-risk cases and predict reliable treatment options for OC. Although anoikis-related genes (ARGs) have been reported to contribute to tumor growth and metastasis, their prognostic value in OC remains unknown. The purpose of this study was to construct an ARG pair (ARGP)-based prognostic signature for patients with OC and elucidate the potential mechanism underlying the involvement of ARGs in OC progression. Methods: The RNA-sequencing and clinical information data of OC patients were obtained from TCGA and GEO databases. A novel algorithm based on pairwise comparison was utilized to select ARGPs, followed by the last absolute shrinkage and selection operator Cox analysis to construct a prognostic signature. The predictive ability of the model was validated using an external dataset, receiver operating characteristic curve, and stratification analysis. The immune microenvironment and the proportion of immune cells were analyzed in high- and low-risk OC cases using seven algorithms. Gene set enrichment analysis and weighted gene co-expression network analysis were performed to investigate the potential mechanisms of ARGs in OC occurrence and prognosis. Results: The 19-ARGPs signature was identified as an important prognostic predictor for 1-, 2-, and 3-year overall survival of patients with OC. Gene function enrichment analysis showed that the high-risk group was characterized by the infiltration of suppressive immune cells and enrichment of adherence-related signaling pathway, suggesting that ARGs involved in OC progression of OC by mediating immune escape and tumor metastasis. Conclusion: We constructed a reliable ARGPs prognostic signature of OC, and our findings suggested that ARGs exerted a vital interplay in OC immune microenvironment and therapeutic response. These insights provided valuable information regarding the molecular mechanisms underlying this disease and potential targeted therapies.